Determination of the Achievement of Self Sufficiency Rice in Meeting the Availability of Nation Rice - Ageng Kurnia , Lendi; Dinar Iskandar, Deden (KnE Social Sciences, 2020)
The priority of the Nawacita Program in the agricultural sector is to increase superior production, especially rice. In achieving these objectives, it is necessary to ensure the availability of national rice. The availability of national rice is fulfilled from 3 aspects, namely local rice production, government rice reserves and rice imports. Most of the previous research, the availability of rice only accounted for local rice production and rice imports. In this study, the government’s rice reserves are counted as one of the main indicators. Because local rice production used to meet people’s needs is always reduced in volume to meet the government’s rice reserves. In achieving rice self-sufficiency, this study also observed how the ability of local rice production to be the only one to supply the availability of national rice, without bringing in from outside parties. Research using the LS method with the Minitab 15.1 program shows the results that partially the availability of national rice is positively influenced by indicators, namely local rice production, rice imports, and the government’s rice reserves. Forecasting the ability of self-sufficiency in rice by relying on local production in supplying the availability of national rice in the future, shows a positive trend meaning the value of the trend of forecasting increases with increasing time. The factors that influence the achievement of rice self-sufficiency are partially determined by rice supply, rice productivity, the gap in rice prices to grain prices, and the use of balanced fertilizers. But it is not influenced by the level of rice consumption in the community. The result of this study indicates that the availability of national rice is still very dependent on local and foreign rice products. However, to achieve rice self-sufficiency in the future, where all needs are met from local products is not impossible, so that dependence on imported rice can be reduced. Keywords: availability of rice, self-sufficiency in rice, production